Race and Ethnicity Influence Survival Outcomes in Women of Caribbean Nativity With Epithelial Ovarian Cancer - Schlumbrecht, Matthew; Cerbon, Danielle; Castillo, Melissa; Jordan, Scott; Butler, Raleigh; Pinto, Andre; George, Sophia (Frontiers in Oncology, 2020)
Background: Caribbean immigrants represent one of the largest groups of minorities in the United States (US), yet are understudied. Racial and ethnic disparities among women with ovarian cancer have been reported, but not in immigrant populations. Our objective was to evaluate differences in the clinicopathologic features and survival outcomes of Caribbean-born (CB) immigrants with ovarian cancer, with special focus on the influence of race and ethnicity on these measures. Methods: A review of the institutional cancer registry was performed to identify women with known nativity treated for epithelial ovarian cancer between 2005 and 2017. Sociodemographic, clinical, and outcomes data were collected. Analyses were done using chi-square, Cox proportional hazards models, and the Kaplan-Meier method, with significance set at p<0.05. Results: 529 women were included in the analysis, 248 CB and 281 US-born (USB). CB women were more likely to have residual disease after debulking surgery (31.2% vs 16.8%, p=0.009) and be treated at a public facility (62.5% vs 33.5%, p<0.001). Black CB women less frequently received chemotherapy compared to White CB women (55.2% vs 82.2%, p=0.001). Among all CB women, Hispanic ethnicity was independently associated with improved survival when adjusting for other factors (HR 0.61 [95% CI 0.39-0.95], p=0.03). White Hispanic CB women had a median overall survival (OS) of 59 months while Black, non-Hispanic CB women had a median OS of 24 months (log-rank p=0.04). Conclusion: Among Caribbean-born women with ovarian cancer, Hispanic ethnicity is significantly associated with improved survival outcomes, regardless of race.